DESIGNING PISA-LIKE MATHEMATICS TASK USING ASIAN GAMES CONTEXT - Ratu Ilma Indra Putri; Zulkardi Zulkardi (Journal on Mathematics Education, 2020)
This study aimed to produce a set of valid, practice and had potential effects of PISA-like mathematics tasks using Asian Games context to support students learning. Design research and lesson study were used as the method both during the design and implementation stages. Target users are 15th years old middle school students from PMRI pilot schools in Palembang. Results show that a set of PISA-like problems on uncertainty and data content are valid, practical, and had a potential effect. Students were doing mathematics in a collaborative, and the learning process becomes meaningful and easily.